Internet addiction and factors associated with it: a cross sectional study among students of a medical college in Davangere, Karnataka - Kumar, Aswin; Nawaz, Ayesha S.; Kumar, Ravi; B. N., Yamuna (International Journal Of Community Medicine And Public Health, 2017)
Background: India is not only growing in terms of population but also developing in terms of communication. Internet has become an essential tool for education, entertainment, communication and sharing of information. Excessive and undisciplined use of internet has led to emergence of internet addiction (IA), especially among students. The objective of the study was to know the magnitude of internet addiction among medical students and to determine the factors associated with it. Methods: The present cross sectional study was carried out over a period of two months among 138 medical students of SSIMS and RC Davangere. Data was collected using a pre designed, pretested questionnaire, with questions adapted from Young’s internet addiction questionnaire to test internet addiction. Results: In our study 30% students had mild internet addiction and 10% had moderate internet addiction. Male gender, internet usage of more than 5 hours per day and expenditure on the monthly internet pack of more than Rs. 400 were found to be significantly associated with internet addiction. Conclusions: More than one third of the students, especially males had internet addiction. It is essential for the parents and institutions to supervise the medical students and limit the time as well as expenditure on the internet usage.